Is well-being everything? Direct and indirect effects of stress and workplace bullying in the Covid-19 pandemic - Muhammad Zulqarnain Arshad; Yunxiao Zhang; Muhammad Ali Arshad; Pittayatorn Kaewkong (Acta Psychologica)
The study investigates the relationship between workplace bullying, stress, and employee well-being, focusing on the mediating role of stress in this dynamic. Using a cross-sectional survey of 310 employees in the Malaysian banking sector, analyzed through structured equation modeling (SEM), the findings reveal that workplace bullying directly elevates stress levels, which in turn adversely affects well-being. Furthermore, stress serves as a significant mediator between workplace bullying and well-being. The research provides implications for organizations and practitioners by bringing out the effects of workplace bullying and stress on the employee. This research assumes more importance in light of COVID-19, as changes in workplaces and the existing level of uncertainty have aggravated the psychological pressures across the world affecting the well-being of employees considerably. Analyzing the research from the psychological and managerial points of view, this research enhances overall knowledge about psychosocial working conditions and provides guidance for management to enhance ways of preventing workplace bullying and increasing staff members' well-being, especially in crisis periods.